Предмет: Алгебра,
автор: alanka077
Докажите, что верно равенство.
(а-х)(а+х) – b(b+2х) – (а-b-х)(а+b+х)=0.
Ответы
Автор ответа:
11
(a-x)(a+x)-b(b+2x)-(a-b-x)(a+b+x)=0
a(a+x)-x(a+x)-b²-2xb-(a(a+b+x)-b(a+b+x)-x(a+b+x))=0
a²+ax-ax-x²-b²-2bx-(a²+ab+ax-ab-b²-bx-ax-bx-x²)=0
a²+ax-ax-x²-b²-2bx-a²-ab-ax+ab+b²+bx+ax+bx+x²=0
-x²+x²=0
0=0
a(a+x)-x(a+x)-b²-2xb-(a(a+b+x)-b(a+b+x)-x(a+b+x))=0
a²+ax-ax-x²-b²-2bx-(a²+ab+ax-ab-b²-bx-ax-bx-x²)=0
a²+ax-ax-x²-b²-2bx-a²-ab-ax+ab+b²+bx+ax+bx+x²=0
-x²+x²=0
0=0
alanka077:
спасибо)0
Похожие вопросы
Предмет: Английский язык,
автор: givlinkovpaschozszti
Предмет: Русский язык,
автор: jixecizagjixeci
Предмет: Русский язык,
автор: 89086443040
Предмет: Алгебра,
автор: Darkkat
Предмет: Математика,
автор: MaXoZaVr